Evaluation of ergonomic risk in dentists providing home care - Genaro, Luís Eduardo [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Valsecki Junior, Aylton [UNESP]; Lopez Rosell, Fernanda [UNESP]; Saliba, Tânia Adas [UNESP] (Taylor & Francis, 2025)
We assessed the risk of Musculoskeletal Disorders (MSDs) in dentists during home-based dental procedures by capturing images of 114 procedures. Work postures were analysed using the Rapid Upper Limb Assessment method. The evaluated procedures included Atraumatic Restorative Treatment (ART), Scaling and Root Planing (SRP), and Oral Hygiene Guidance (OHG). A significant association was observed between wrist scores and female sex (p = 0.001), indicating a moderate risk for MSDs. SRP showed significant associations with arm (p = 0.009), wrist (p = 0.029), neck (p = 0.008), and legs (p = 0.012). The final MSD risk classification was significantly associated with SRP (p = 0.032), revealing that 25.5% of the procedures had moderate risk, 38.7% high risk, and 35.8% very high risk for MSDs. Dentists who provide home care may have a moderate to high risk of developing MSDs, which is associated with the type of procedure.
Keywords: Dentist; home care; occupational risks; Unified Health System